A blistering eruption of the head and neck in an 18‐year‐old. (1st July 2022) - Timoney, Irene; Porter, Emma; Leonard, Niamh; Uddin, Aleem; Lynch, Maeve
Abstract: An 18‐year‐old presented with an atypical blistering eruption. Direct immunofluorescence microscopy of perilesional skin showed strong linear deposition of IgG and C3 at the dermoepidermal junction. Her presentation was unusual and posed a diagnostic challenge, as this condition is very rare in this age group.